Controlled, Uncontrolled Communication, Brand Name and Brand Attitude: A Relational Study on Cellular Telecom Sector of Bangladesh - Ahmed, Jubayer; Rouf, Md. Abdur (American Journal of Trade and Policy, 2014)
The main objectives of the study is to examine the impact of communication variables like controlled communications, uncontrolled communications and brand name on brand attitude in the context of Grameen Phone Telecom. A systematic sampling method was adopted to collect data from the respondents. A total number of 100 questionnaires were distributed, and 93 completed (usable) questionnaires were considered for statistical analyses and research hypotheses testing. The researcher used statistical techniques like mean, standard deviation, correlation and regression analysis. The results of regression analysis are show that controlled communication and brand name are statistically and significantly associated to brand attitude. These results provided full support to research hypotheses 2 and 3. Uncontrolled communication failed to enter into the regression table which indicates that uncontrolled communication is not statistically and significantly associated to brand attitude. The results of regression analysis provided no support for research hypothesis-1. JEL Classification: M31, M37